2022
DOI: 10.3390/foods11071060
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Their Metabolites in Renal Diseases: An Overview

Abstract: Kidney diseases constitute a worldwide public health problem, contributing to morbidity and mortality. The present study aimed to provide an overview of the published data regarding the potential beneficial effects of polyphenols on major kidney diseases, namely acute kidney injury, chronic kidney disease, diabetic nephropathy, renal cancer, and drug-induced nephrotoxicity. This study consists of a bibliographical review including in vitro and in vivo studies dealing with the effects of individual compounds. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 205 publications
0
12
0
7
Order By: Relevance
“…Polyphenols have important anti-oxidant properties as demonstrated by several studies and reports [ 20 , 21 , 22 , 23 ]. These properties presented them as major compounds in the prevention and treatment of chronic disease including cancer, cardiovascular disease (CVD), neurodegenerative disorders, diabetes, and renal failure [ 24 , 25 , 26 , 27 ]. Phenolic compounds are extensively distributed in plants and exhaustive studies demonstrated their benefits and curative potential, including antioxidant, anti-microbe, anti-neoplasic, and anti-inflammatory effects [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols have important anti-oxidant properties as demonstrated by several studies and reports [ 20 , 21 , 22 , 23 ]. These properties presented them as major compounds in the prevention and treatment of chronic disease including cancer, cardiovascular disease (CVD), neurodegenerative disorders, diabetes, and renal failure [ 24 , 25 , 26 , 27 ]. Phenolic compounds are extensively distributed in plants and exhaustive studies demonstrated their benefits and curative potential, including antioxidant, anti-microbe, anti-neoplasic, and anti-inflammatory effects [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are also important anti-cancer agents [ 79 ]. Tea polyphenol compounds were proven in many animal models to prevent various types of cancers, e.g., ovarian, breast, pancreas, colorectal, oesophagus, liver, lung, and kidney cancers [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Moreover, in vitro studies have demonstrated that the anticancer activity of polyphenols relies on their ability to inhibit growth or stimulate apoptosis in various cancer cell lines, such as HL60 human promyelocytic leukaemia cells, A431 epidermoid carcinoma cells, LNCaP and androgen-insensitive PC-3 human prostate carcinoma cells, human prostate cancer LNCaP cells, OVCA 433 human ovarian cancer, HepG2 cells, Caco-2 human colon cancer cells, human pancreatic carcinoma cell line Mia PACA-2, and oestrogen-independent MDA-MB-435 and oestrogen-dependent MCF-7 breast cancer cell lines [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Polyphenols In Disease Prevention and Treatmentmentioning
confidence: 99%
“…They are mangiferin, syringaresinol, resveratrol, and gallic acid. These compounds regulate signaling cascades including those engaged in response to oxidative stress, anti-inflammatory, and apoptosis [ 62 ].…”
Section: Bioactive Phytochemicals For Dnmentioning
confidence: 99%